2018
DOI: 10.1111/cid.12586
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal analysis on the effect of insertion torque on delayed single implants: A 3‐year randomized clinical study

Abstract: Present findings showed that implants placed with higher insertion torque in mandible led to greater bone resorption and mucosal recession than that registered for implants placed with a regular IT. Moreover, sites with a thick buccal bone wall (≥1 mm) showed smaller recession at the facial soft tissue level after 3 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
86
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(91 citation statements)
references
References 46 publications
5
86
0
Order By: Relevance
“…Those results are consistent with the recent work of Marconcini et al 14 in which implants placed with high IT (>50 Ncm) exhibited invariably significant crestal bone loss and soft tissue recession compared to implants placed with regular IT at 3-year follow-up. A similar trend was detected in the earlier follow-up of the same group of implants at 1 and 2 years.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Those results are consistent with the recent work of Marconcini et al 14 in which implants placed with high IT (>50 Ncm) exhibited invariably significant crestal bone loss and soft tissue recession compared to implants placed with regular IT at 3-year follow-up. A similar trend was detected in the earlier follow-up of the same group of implants at 1 and 2 years.…”
Section: Discussionsupporting
confidence: 93%
“…Animal studies did not show a negative effect on osseointegration in high IT group (up to 150 Ncm), 10 , 11 whereas human studies showed controversial results. 12 14 A recent systematic review indicated that there is no significant difference in bone resorption and implant failure rate between implants placed with high IT (up to 176 Ncm) and low (30 Ncm). 15 However, the authors reported that most studies have a high risk of bias.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study of the same group with longer follow‐up (3 years) has observed similar results in terms of bone resorption and a 98.2% success rate in implants placed with regular IT and 91.3% when high IT. These results demonstrated the importance of pay attention on implant placement protocols (Marconcini et al, ).…”
Section: Discussionmentioning
confidence: 75%
“…Numerous variables, including patient habits [ 45 ], surgical technique [ 46 ], soft tissue and alveolar bone thickness [ 47 49 ], implant and abutment design (e.g., macro- and microgeometry, connection characteristics, implant crest module, and abutment height) [ 50 53 ], number of abutment disconnections [ 54 ], and prosthetic features (e.g., screwed versus cemented retention, inadequate occlusion) [ 55 , 56 ] have been identified as influencing factors in the genesis of peri-implant bone resorption. However, due to their simultaneous action, the exact role and importance of each factor, together with their complex interactions, are not completely clarified yet [ 57 ].…”
Section: Discussionmentioning
confidence: 99%